Experimental investigation of leakage flow in centrifugal blood pump - Tay, Wen Bin (2014)
The study of leakage flow is essential in the design of a good centrifugal blood pump. A good wash out at high volumetric efficiency will prevent thrombus1 formation, while excessive leakage flow results in undesirable hemolysis2. To design a good centrifugal blood pump, a good combination of the impeller rotational speed and clearance gap is necessary.